Edible Cyanobacterial Genus Arthrospira: Actual State of the Art in Cultivation Methods, Genetics, and Application in Medicine - Furmaniak, Magda A.; Misztak, Agnieszka E.; Franczuk, Martyna D.; Wilmotte, Annick; Waleron, Małgorzata; Waleron, Krzysztof F. (Frontiers in Microbiology, 2017)
The cyanobacterial genus Arthrospira appears very conserved and has been divided into five main genetic clusters on the basis of molecular taxonomy markers. Genetic studies of seven Arthrospira strains, including genome sequencing of seven strains, have enabled a better understanding of those photosynthetic prokaryotes. Even though genetic manipulations have not yet been performed with success, many genomic and proteomic features such as stress adaptation, nitrogen fixation or biofuel production have been characterized. Many of above-mentioned studies aimed to optimize the cultivation conditions. Factors like the light intensity and quality, the nitrogen source or different modes of growth (auto-, hetero- or mixotrophic) have been studied in detail. The scaling-up of the biomass production using photobioreactors, either closed or open, was also investigated to increase the production of useful compounds.. The richness of nutrients contained in the genus Arthrospira can be used for promising applications in the biomedical domain. Ingredients such as the calcium spirulan, immulina, C-phycocyanin and γ-linolenic acid (GLA) show a strong biological activity. Recently, its use in the fight against cancer cells was documented in many publications. The health-promoting action of 'Spirulina' has been demonstrated in the case of cardiovascular diseases and age-related conditions. Some compounds also have potent immunomodulatory properties, promoting the growth of beneficial gut microflora, acting as antimicrobial and antiviral. Products derived from Arthrospira were shown to successfully replace biomaterial scaffolds in regenerative medicine. Supplementation with the cyanobacterium also improves the health of livestock and quality of the products of animal origin. They were also used in cosmetic preparations.